(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Visual function impairment in early childhood affects the development of child’s perception of the world. There is an increase in the importance of studies on not only characteristics of vision impairment, but also on the impact of these characteristics on the quality of life (QoL), for predicting subsequent full-blown socialization of the child and the potential for effective treatment of a detected eye condition or correction of an eye with a refractive error. Purpose: To examine the impact of eye disease on the components of QoL of children from various age groups. Material and Methods: Eight hundred and twenty-four parents of children of various age groups voluntarily and anonymously responded to the adapted version of the Children’s Visual Function Questionnaire (CVFQ) while their children were having an examination of eye functions. Results: The presence of eye disease affected child QoL, with a reduction in the mean total score of child QoL of 17.8% for the age cohort of children under 3 years of age, and of 19.3% for the age cohort of children above 3 years of age. Visual function impairment affected the scores of General Health, General Vision, Competence and Personality domains, particularly, the score of the child’s capacity to get along well with peers and friends. Conclusion: Studies on child quality of life demonstrate the impact of visual function impairment on the child’s potential for socialization, and still provide a means for getting feedback from the patient when there is a need for prolonged observation of changes in his/her visual functions.